2015
DOI: 10.4103/0253-7176.150816
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Stress as a Risk Factor for Substance use Disorders: Clinical and Neurobiological Substrates

Abstract: Background:Early Life Stress (ELS) can profoundly influence an individual's genotype and phenotype. Effects of ELS can manifest in the short-term, late life and even in subsequent generations. ELS activate corticotrophin releasing factor (CRF); CRF influences drug seeking and addiction. The aim of this study was to examine the effects of endogenous elevated levels of CRF on addiction.Materials and Methods:Inducible forebrain over-expression of CRF mice (tetop-CRH x CaMKII-tTA) was used for this study. Morphine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…A review of RCT data shows that mindfulness interventions for SUDs are at least as effective as other evidence-based interventions and perhaps particularly helpful in patients with comorbid anxiety or depression (Korecki et al, 2020). These findings align with our prior studies highlighting the link among chronic stress, CNS dysregulation, and SUDs (Varghese et al, 2015; Varghese et al, 2019). Likewise, we have previously published on the benefit of mindfulness-based treatments in patients with SUDs and other psychiatric illnesses (Varghese et al, 2014; Varghese et al, 2021).…”
supporting
confidence: 93%
“…A review of RCT data shows that mindfulness interventions for SUDs are at least as effective as other evidence-based interventions and perhaps particularly helpful in patients with comorbid anxiety or depression (Korecki et al, 2020). These findings align with our prior studies highlighting the link among chronic stress, CNS dysregulation, and SUDs (Varghese et al, 2015; Varghese et al, 2019). Likewise, we have previously published on the benefit of mindfulness-based treatments in patients with SUDs and other psychiatric illnesses (Varghese et al, 2014; Varghese et al, 2021).…”
supporting
confidence: 93%
“…Fahlke et al, (2000) found that non-human primates stressed in early life (i.e., maternal deprivation) exhibited elevated cortisol levels in response to stressors, which was associated with increased alcohol self-administration (Fahlke et al, 2000). A hyperactive stress response is also linked to increased drug sensitivity and greater withdrawal symptoms in preclinical models (Varghese, Montalvo-Ortiz, Csernansky, Eiger, Herrold, Koola, et al, 2015). These studies converge to suggest that dysregulation of the HPA axis (both blunting and hyperactivity), in general, may serve as a biomarker for risky substance use behaviors, as well as a pre-morbid risk factor for developing SUDs.…”
Section: Hpa Axis and Crf Brain Systemsmentioning
confidence: 99%
“…For example, CRF overexpression leads to increased PDYN protein in mice after morphine administration [ 86 ]. Moreover, while certain neuropeptides are linked to “pro-stress” responses and alcohol addiction, their variation during alcohol withdrawal is not uniform.…”
Section: Discussionmentioning
confidence: 99%